Biological effectiveness and relative biological effectiveness of ion beams for in‐vitro cell irradiation. Issue 8 (20th June 2022) - Li, Heng
Abstract: Biological effectiveness and relative biological effectiveness are critical for proton and ion beam radiotherapy. However, the relationship between the two quantities and physical character of ion beams is not well established. By analyzing 1188 sets of in‐vitro cell irradiation experiments using ion beams ranging from protons to 238 U, compiled by the Particle Irradiation Data Ensemble (PIDE) project, the biological effectiveness of the ion beams, with cell survival fractionation (SF) as the endpoint, was found to be dependent on the fluence and linear energy transfer (LET) of the ion beam. Consequently, the relative biological effectiveness of the ion beam to photon beam was also established as a function of LET. A common form of relationship among SF, fluence, and LET was found to be valid for all ion beam experiments. The close form relationship could be used for proton and ion beam radiotherapy applications. Abstract : This study for the first time established the relationship between post irradiation cell survival and physical character of an ion beam. The relationship is readily applicable and critical for proton and ion beam radiotherapy.